Zwingli - Potter, G. (Cambridge University Press, 1976)
Huldrych Zwingli was widely known as a humanist and admirer of Erasmus when he came to Zurich from Glarus and Einsiedeln in 1519. The stages of the Zwinglian Reformation there were marked by the attack on compulsory fasting, images in churches and the doctrine of purgatory, culminating in the rejection of the sacrificial nature of the mass. Like Luther, Zwingli accepted sola scripture as the only criterion by which religious beliefs were to be judged, but he parted company with Luther on the central issue of the nature of the eucharist. Their confrontation at Marburg failed to bring about agreement. A further important challenge came from the Anabaptists, who rejected infant baptism, military service, oaths and payment of tithe. Zwingli's many verbal and written discussions with them and his relations with Grebel, Mentz, Blaurock and Hubmaier form part of the story.